Advancing formative assessment in every classroom : a guide for instructional leaders - Moss, Connie M.; Brookhart, Susan M. (Alexandria, VA : ASCD, 2009)
Explains formative assessment, discusses common misconceptions about it, and provides strategies for using it in the classroom.
The lay of the land: essential elements of the formative assessment process -- Leveling the playing field: sharing learning targets and criteria for success -- Shifting from correcting to informing: feedback that feeds forward -- Achieving more with focus: fostering student goal setting -- Helping goal-setters become active goal-getters: the role of student self-assessment -- Enriching classroom discourse: planning for and asking strategic questions -- Valuing critical thinking and inquiry: engaging students in asking effective questions -- Creating a culture of intentional learning: taking formative assessment schoolwide.
Includes bibliographical references (p. 152-157) and index.
Professional
Keywords: Educational evaluation -- United States; Group work in education -- United States; Teachers -- In-service training; Cooperative learning; Educational evaluation -- United States; Teachers -- In-service training